The frequency of premenstrual syndrome (PMS) and its association with body mass index (BMI) in female students attending universities in Iraq - Ahmed Majeed.M , Saja Jasem Abd-Ali (Cuestiones de Fisioterapia, 2025)
Premenstrual syndrome, or PMS, is a common issue that impairs the performance and quality of life of young women. It is characterized by the onset of cyclical emotional, psychological, and physical symptoms that subside once menstruation has ended and start during the luteal (premenstrual) phase of the menstrual cycle. The Body Mass Index (BMI) is a tool for identifying weight categories that could make medical conditions worse.